1983
DOI: 10.1128/aem.45.4.1402-1404.1983
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of D-xylose and D-glucose isomerase activities in Escherichia coli by gene cloning

Abstract: A recombinant plasmid, designated pUC1002, was constructed by ligation of a HindIlI restriction endonuclease fragment of Escherichia coli chromosomal DNA to vector plasmid pMB9. Strains carrying this plasmid were selected by transformation of an E. coli strain bearing the xyl-7 mutation to a xylose-positive (Xyl+) phenotype. Strains containing pUC1002 produced coordinately elevated levels of D-xylose isomerase and D-xylulose kinase. Under appropriate conditions, the isomerase also efficiently catalyzed the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Chromosomal fragments with the ability to complement all three different classes of xyl-negative mutants were cloned on a plasmid. Localization of the genes indicated that the putative xylulose kinase gene resides near the glucose isomerase gene, which is consistent with the organization of the locus in Salmonella typhimurium (73), E. coli (186), and Bacillus subtilis (183) (Fig. 4).…”
Section: Genetic Regulation Of Glucose Isomerase Biosynthesissupporting
confidence: 80%
See 1 more Smart Citation
“…Chromosomal fragments with the ability to complement all three different classes of xyl-negative mutants were cloned on a plasmid. Localization of the genes indicated that the putative xylulose kinase gene resides near the glucose isomerase gene, which is consistent with the organization of the locus in Salmonella typhimurium (73), E. coli (186), and Bacillus subtilis (183) (Fig. 4).…”
Section: Genetic Regulation Of Glucose Isomerase Biosynthesissupporting
confidence: 80%
“…The first report on the isolation of the GI gene was from E. coli by Ho et al (84). D-Xylose isomerase and xylulokinase activities were amplified by transformation of a GIdeficient E. coli strain with plasmid pMB9 bearing a HindIII restriction fragment of E. coli chromosomal DNA (186). The GI gene from E. coli was sequenced and was shown to code for GI by purification of the cloned gene product (142).…”
Section: Homologous Hostsmentioning
confidence: 99%
“…This indicated that TG1, DH5a, JM109 and BL21(DE3) strains utilize xylose via the pentose phosphate pathway, whereas HB101 could not. E. coli strains which could utilize xylose also could utilize D-xylulose via xylose isomerase (EC.5.3.1.5) [11]. Considering that strain TG1 grew faster than DH5a, JM109 and BL21 in a minimal medium containing xylose as the sole carbon source (data not shown), we selected TG1 as the host for cloning the ArDH gene from G. oxydans CGMCC 1.110.…”
Section: Resultsmentioning
confidence: 99%
“…Wovcha et uf. [21] reported the amplification of xylose isomerase activity by cloning of a 13 kb Hind111 E. coli chromosomal DNA fragment that carried the x y l A gene. E. coli JC1553 (xy17) with cloned x y l A carried on pMB9 exhibited a fivefold increase in xylose isomerase activity over the wild type strain.…”
Section: Discussionmentioning
confidence: 99%